From Kartini Kebaya to National Clothing: The Development of Indonesian Women's National Fashion from the 19th to the 24th Century - Maziyah, Siti; Kumalasari, Ratih (Proceedings International Conference of Culture and Sustainable Development; Vol 2 (2024): PROCEEDINGS ICOCAS, 2024)
The issue of kebaya has recently become an interesting topic of discussion because apart from Indonesia, several neighboring countries also have traditional clothing similar to kebaya. Even Malaysia, Singapore, Brunei Darussalam, and Thailand have registered their kebaya as intangible cultural heritage to UNESCO. The problem in this article is how the Kartini kebaya became the national clothing in Indonesia. This research aims to understand the process of kebaya as Javanese traditional clothing becoming national clothing in Indonesia. The relevance of this research is related to kebaya as an Indonesian cultural product that has become an icon of the Indonesian nation. The research method used is by using historical methods that begin by tracing the origin of kebaya in Java and Indonesia, as well as its development until it is designated as the national clothing of Indonesian women. The results of the study show that the Kartini kebaya is one of the types of women's clothing in Indonesia that is polite and makes the wearer look elegant and authoritative, in accordance with the personality of the Indonesian nation. All women in Indonesia accept this type of clothing as their national clothing
Keywords: Kebaya Kartini, national clothing, Indonesian women, national personality